IMPORTANCE OF PHYSICAL EXAMINATION IN EARLY DETECTION OF LUMP IN BREAST IN WOMEN OF DIFFERENT AGE GROUPS - Abbas, Hafsa; Imran, Saira; Waris, Noorul -ain-Hafeez; Khanam, Andleeb; Khurshid, Rukshshan (Journal of Ayub Medical College Abbottabad, 2010)
Background: The spectrum of breast lesions in adolescents varies markedly from that for adults, with the former lesions being overwhelmingly benign. Fine needle biopsy can be used to distinguish benign and malignant tumour. Study Design: This study examined the characteristics and outcome of women with different age groups in whom physical examination was their sole method of lump in breast detection. Patients and Methods: A total of 200 patients were included in the study. These were divided into 3 groups. Group A was consisting of 75 girls with age of pubescent. Group B included 69 suspected breast cancer women with age range 26-38 years. Fifty-six suspected breast cancer women with age range 41-60 year were included as group C. Study was carried out in patients admitted in the Department/Out-door of Surgery, Sir Ganga Ram Hospital, Lahore, Pakistan. Study period was 6 months. All women received a physical examination by a breast surgeon. Proforma including demographic and clinical characteristics were filled. The diagnosis for patients in this study was achieved by core needle biopsy using a 14-gauge cutting needle. Results: It was observed that early age at menarche (<15 year) plays an important role in developing both type of tumour, i.e., benign or malignant. Body Mass Index (BMI) with a range of 19-25 may be a risk factor in developing both type of tumours especially in pubescent and reproductive age, while BMI>25 may be a risk factor in peri/post menopausal women. Active life style is more important with increasing age as it decreases the risk of developing tumour state. Family history was more common in women with peri/post menopausal status as compared to other age groups. Clinical characteristics showed that lump size <2.5 cm was more common in both pubescent and reproductive age. While lump size with a range of 2.5-5.0 cm, was observed in all groups of patients. Fibroadenoma is observed in almost all women with pubesenct age while both benign and malignant tumour observed in women with reproductive age. Malignant tumour was observed mostly in women with peri/post menopausal status. Conclusion: Study concluded that early detection or clinical examination with FNA cut out the patients from harassment of malignancy and complications especially in the pubescent age. It is also found that Physical examination remain the useful indicators of prognosis in diagnosing cancer. Further research is needed to fully understand the reasons for variations in breast disease outcomes i.e. malignant or benign. Keywords: Breast cancer, Fibroadenoma, Physical examination